EFEK VENTURI PADA PIPA PENDISTRIBUSIAN AIR BERSIH DINAS CIPTA KARYA DAN TATA RUANG KE PASAR BELAKANG PADANG - Fealy Chia (Racic : Rab Construction Research, 2018)
This research aims to determine whether there is an effect on venture in the pipe and find for the speed of water, water discharge, and the character flow on a pipe. The location of pipe under research is in Belakang Padang, one of the sub-districts in Batam City. Primary data is obtained from observing directly from the rear distribution pipeline in Belakang Padang, while secondary data is obtained from Cipta Karya and Tata Ruang Belakang Padang. Based on primary and secondary data and through the calculation process, the results of the speed in the 4 inch pipe are 2,469 m/s, the 2 inch pipe is 9,896 m/s, and the pipe ¾ is 71,3929 m/s. The water discharge in the 4 inch pipe is 0,02 m3/s, the 2 inch pipe is 0,01999 m3/s, and the ¾ inch pipe is 0,01999 m3/s. The flow properties that obtained by calculation of Reynolds Number in the 4 inch pipe are turbulent with a value of 139361,33, in the 2 inch pipe is 279287,11 which means the turbulent flow, and pipe ¾ is 755574,86 with turbulent flow.